The contribution of the ILESSI-DCF Model to promote creative thinking skills of Madrasah Aliyah (MA) students - Ahmad Khoiri; Achmad Affandi; Mohd Fauzi Sedon; Che Nidzam Che Ahmad; Qori Agussuryani; Ayu Mar'ati Barokatun Ni'mah (Momentum: Physics Education Journal, 2023)
Dieng Culture Festival (DCF) is considered as the symbol of cultural wealth owned by the local people of Wonosobo, Central Java Province, Indonesia. The reconstruction of indigenous knowledge (indigenious science) of Dieng Plateau people is hardly integrated into science learning. Meanwhile, creative thinking skills as a demand for 21st century skills are urgently needed in students' lives. One of the learning models recommended by the 2013 curriculum is the inquiry lesson model. The ILESSI-DCF (Inquiry Lesson Based Ethno Socioscientific Issues-Dieng Culture Festival) model is an inquiry model constructed with the Socioscientif Issues (SSI) strategy and an ethnoscientific approach. This study aims to analyze the contribution of the ILESSI-DCF (Confrontation, Observation, Recognition, Explanation, Application) syntax in promoting creative thinking skills. The research method used quasi-experimental with the type of independent sample t-statistical design. The research sample consisted of two MA (Madrasah Aliyah) namely MA A, totaling 60 students (experimental group 29 students, control group 31 students), and MA B totaling 64 (sixty four) students (experimental group 32 students, control group 32 students). The data collection method used creative thinking skills test questions. The data analysis technique used SPSS 25.0 on the MANOVA test to analyze the extent to which each syntax of the ILESSI-DCF Model contributed. The results showed that the overall contribution of each syntax of the ILESSI-DCF Model was effective in promoting creative thinking skills. The contribution of the ILESSI-DCF Model syntax has the greatest contribution to syntax 3, namely the reconstruction of students in MA A with a mean of 12.10 when compared to the other syntaxes, while the lowest contribution to syntax 1 Confrontation in MA B with 9.68. The results of the ILESSI-DCF Model syntax contribution very diverse and being influenced by differences in students' cultural backgrounds in reconstructing science action. The implications of research into the contribution of the ILESSI-DCF Model syntax to the ability to reconstruct people's original science into scientific knowledge is very important for realizing character education that respects diversity through the creative thinking skills of MA students.